MODERN RELIEF MODELING METHODS - Isamiddin Fattievich Buranov (International Journal on Orange Technologies, 2021)
The article discusses various methods of modeling the relief used in the practice of engineering and design work. In particular, the geometrical, mathematical and digital representation of the relief is considered.